Structural bank regulation initiatives approaches and implications - Gambacorta, Leonardo; Rixtel, Adrian A. R. J. M. van 1962- (Bank for Internat. Settlements, 2013)
The paper examines the basic rationale and features of the proposals adopted to separate specific investment and commercial banking activities (Volcker rule, Vickers and Liikanen proposals). In particular, it focuses on the likely implications of such initiatives for: (i) financial stability and systemic risk; (ii) banks' business models; and (iii) the international activities of global banks.
Parallel als Online-Ausg. erschienen